Proyecto colaborativo y actitud democrática en estudiantes de cuarto grado de educación secundaria de la Institución Educativa “Santa Rosa”-Trujillo - Sanchez Rodriguez, Mariela Giovana (2019)
ABSTRACT The present research was carried out with the purpose of determining the extent to which the PODA Collaborative Project improves the democratic attitude in the fourth grade students of the "Santa Rosa" Educational Institution of Trujillo, 2017. The research included a study population of 434 students and the sample consisted of 84 students; 42 in the experimental group and 42 in the control group; which have similar age and characteristics. The collaborative project PODA, is constituted by four dimensions, thought, opinion, decision and action; and was implemented as a learning strategy in the classroom for the area of Person, Family and Human Relations, Civic and Civic Education and in the Social Sciences in general. It was based on Habermas's Critical Theory, Feuerstein's Mediated Learning Theory, Rogers Humanist Pedagogy, for the independent variable of Collaborative Project PODA and for the variable of Democratic Attitude, the Model of Democratic Citizenship of Ruiz, Theory of Social Learning of Bandura, and the Three-dimensional Model of McGuire, Becker Chaiken and Stangor. In its execution, the quasi-experimental design was used to determine the improvement of the democratic attitude in the students studied. The analysis of the results made it possible to verify that the PODA Collaborative Project significantly improves the democratic attitude in the students studied.